(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
The emergence of sensor technologies and embedded devices has created significant potential for autonomous accident-detection systems that will enhance emergency response and road safety. In this paper, an automated accident detection system is proposed that rapidly notifies the emergency center of the accident’s location and severity. Five sensors, such as a gyroscope, an IR flame sensor, a glass-break sensor, a smoke sensor, and a vibration sensor, are integrated with the STM32 microcontroller board. An algorithm is proposed with three severity levels based on the activation of a sensor or group of sensors. Emergency responders can prioritize their interventions by categorizing accidents into severity levels, thereby allocating resources more efficiently and effectively. The proposed method offers significant potential to strengthen road safety and enhance emergency response to road accidents.